Association between erectile dysfunction and the predicted 10-year risk for atherosclerosis cardiovascular disease among U.S. men: a population-based study from the NHANES 2001-2004 - Mei, Yangyang; Chen, Yiming; Wang, Xiaogang; Xu, Renfang; Xu, Rui; Feng, Xingliang (Frontiers in Endocrinology, 2024)
BackgroundErectile dysfunction (ED) is considered the tip of the iceberg for cardiovascular disease (CVD). However, there is still conflicting evidence regarding their relationship. Recently, a validated tool for the Atherosclerotic Cardiovascular Disease (ASCVD) risk score has provided a key opportunity to delve deeper into the relationship between ED and CVD. Therefore, we intended to assess the relationship between ED and 10-year ASCVD risk scoreMethodsComplete data of 1207 participants from the 2001-2004 National Health and Nutrition Examination Survey (NHANES) were used in the study. Various weighted logistic and linear regression models were employed to investigate the effect of the presence of ED on the higher 10-Year ASCVD risk score or high risk of 10-Year ASCVD. Conversely, logistic regression models were repeated to explore the effect of continuous or categorical ASCVD risk score on the prevalence of ED. Sensitivity analyses were also conducted, focusing on severe ED with a more stringent definition. Additionally, we supplemented our study with subgroup analyses, restricted cubic spline (RCS) analysis, and receiver operating characteristic (ROC) analysis to enhance the robustness of our results.ResultsParticipants with ED had higher ASCVD risk scores and a higher risk of ASCVD, which corresponded to a greater prevalence of ED or severe ED. When considering the presence of ED as the exposure, our results indicated that the presence of ED increased the ASCVD risk score (Model 3: β [95%CI]: 2.09 [1.12, 3.06]) in Model 3, as well as the high risk of ASCVD (OR [95%CI]: 2.27 [1.13, 4.59]). Conversely, a continuous increase in the ASCVD risk score was also associated with an increased prevalence of ED (OR [95%CI]: 1.04 [1.02,1.06]). Additionally, those in the borderline ASCVD risk group (OR [95% CI]: 2.95 [1.60, 5.44]), intermediate ASCVD risk group (OR [95% CI]: 4.53 [2.35, 8.73]), and high ASCVD risk group (OR [95% CI]: 7.62 [3.19, 18.19]) exhibited progressively increasing ED risk when compared to the low-risk group. Furthermore, the RCS analysis demonstrated a linear relationship between ED prevalence and the continuous ASCVD risk score, with the latter showing high efficacy in predicting ED (AUC [95%CI]: 0.794 [0.768, 0.821]).ConclusionsThe presence of ED may precede the onset of ASCVD by some years. Consequently, timely and dynamic evaluation of the cardiovascular status provides an earlier opportunity to identify and implement effective prevention strategies to promote cardiovascular health for ED patients.